"Bioelectrical impedance analysis in managing sarcopenic obesity in NAFLD". (6th May 2021) - Hanna, David J.; Jamieson, Scott T.; Lee, Christine S.; Pluskota, Christopher A.; Bressler, Nicole J.; Benotti, Peter N.; Khurana, Sandeep; Rolston, David D. K.; Still, Christopher D.
Abstract: Introduction: Sarcopenic obesity and its association with nonalcoholic fatty liver disease (NAFLD) is under‐recognized by many healthcare providers in Western medicine due to the lack of awareness and diagnostic guidelines. The result is delayed recognition and treatment, which leads to further health deterioration and increased healthcare costs. Sarcopenic obesity is characterized by the presence of increased fat mass in combination with muscle catabolism related to chronic inflammation and/or inactivity. Previous research has recommended evaluating body composition and physical function performance to adequately diagnose sarcopenic obesity. Body composition analysis can be performed by imaging applications through magnetic resonance imaging, computed tomography, and dual‐energy x‐ray absorptiometry. Due to the cost of each device and radiation exposure for patients as evidenced in all three modalities, bioelectrical impedance analysis offers a noninvasive approach capable of providing quick and reliable estimates of lean body and fat mass. Methods and Results: This review analyzes the current evidence‐based literature, indicating a lower skeletal muscle mass and increased visceral adipose tissue correlation to the advancement of fibrosis in fatty liver disease. Conclusion: Given the substantial promising research conducted in predominantly Asian populations regarding body tissue distribution and NAFLD, additional prospective research is needed to extend these findings in Western populations.